Minimally Invasive L5-S1 Oblique Lumbar Interbody Fusion With Simultaneous Robotic Single Position Posterior Fixation: 2-Dimensional Operative Video. Issue 6 (25th August 2021) - Pham, Martin H; Gupta, Mihir; Stone, Lauren E; Osorio, Joseph A; Lehman, Ronald A
Abstract: The unique anatomy at L5-S1 presents different challenges and considerations to be made when compared to other areas in the lumbar spine. In this way, the oblique lumbar interbody fusion (OLIF) is more closely related to a supine anterior lumbar interbody fusion (ALIF) except that the former is performed in a lateral position down a smaller minimally invasive retroperitoneal corridor. This lateral positioning at L5-S1, however, provides an opportunity for single-position surgery simultaneously with posterior fixation, which is not afforded by other approaches.  We present here a case of a 57-yr-old male with a prior right-sided L5-S1 microdiscectomy who presents with worsening lumbar radiculopathy and foot drop. He subsequently underwent a minimally invasive L5-S1 OLIF with posterior instrumentation placed bilaterally while remaining in a single lateral position (Mazor X Stealth Edition, Medtronic, Dublin, Ireland). Both the anterior OLIF surgeon and posterior instrumentation surgeon were able to work simultaneously. There is currently a need for further high-quality operative videos showing the L5-S1 OLIF technique, and to our knowledge, this is the first video demonstrating a 2-surgeon near-simultaneous workflow approach using a spinal robotics platform at this level.  There is no identifying information in this video. A patient consent was obtained for the surgical procedure and for publishing of the material included in the video.